SERUM PROGESTERONE AND OVULATION TIME IN COWS PRESENTED FOR AI AND THE SUBSEQUENT PREGNANCY RATE - EZHILARASAN, C; MURUGAVEL, K; ANTOINE, D; RAJU, MS (The Indian Journal of Animal Reproduction, 2022)
Serum progesterone at the time of AI, ovulation time and the subsequent pregnancy rate was investigated in 68 crossbred Jersey cows presented for AI (day 0). Ovarian ultrasonography was carried out, a) to record preovulatory follicle (POF) on day 0, b) disappearance of POF on day 1 or day 2 after artificial insemination (AI), c) to confirm ovulation on day 12 post-AI, and d) on day 27 to confirm pregnancy. Serum progesterone was estimated from the blood samples collected on day 0. Ovulation rate in cows was 91.2% (n=62/68). Out of these, the percentage of cow that ovulated between 0-24h (67.6%) was higher (p
Keywords: Crossbred cows; Estrus; Ovulation time; Pregnancy rate; Progesterone